Violation of the weak equivalence principle in Bekenstein's theory - Kraiselburd, Lucila (2011)
Bekenstein has shown that violation of Weak Equivalence Principle is strongly suppressed in his model of charge variation. In this paper, it is shown that nuclear magnetic energy is large enough to produce observable effects in Eötvös experiments.